Restructuring Hospital Management in Labuan Bajo as A Strategy to Remedy the Impact of Covid-19 Pandemic - Elisabet Oktaviani Hanggu; Gregorius Antariksa Berybe (International Journal of Applied Sciences in Tourism and Events, 2022)
The purpose of the study is to determine the methods used by hotels in dealing with the crisis caused by the Covid 19 pandemic and assess their impacts. This is descriptive qualitative research focused on describing the strategies implemented by these hotels and the data obtained were analyzed through 1) description or orientation, 2) reduction, and 3) selection stages. The process involves comprehensively understanding the focus set and analyzing the direction of the problem. Moreover, the result which was in the form of a theme obtained from the data was constructed into knowledge, hypotheses, and even new theories. It is important to note that the Labuan Bajo hotel deserted due to COVID-19 was used as a case study in providing innovation or new ways of managing hospitality to ensure the survival of the business. This is necessary because active incomes are only obtained through guest visits and tourists’ patronage but are ineffective due to restrictions made by the government on tourism activities. It was eventually recommended that hotels in Labuan Bajo need to continue meeting operational needs during the pandemic. Furthermore, the Hospitality Management Restructuring strategy implemented to deal with the Covid 19 crisis was considered quite successful by hoteliers in Labuan Bajo because it positively impacted the sustainability of the hotel business during the pandemic.